Book Reviews (The ecumenical review, 1954)
Book reviewed in this article: “ECUMENICAL” — BY AN ARCH-ECUMENIST: The Meaning of Ecumenical, by W. A. Visser ‘t Hooft WHAT ARE THE ECUMENICAL GOALS?: The Unfinished Reformation, by Charles Clayton Morrison THE MESSAGE OF WILLINGEN: The Missionary Obligation of the Church. Willingen THE MESSAGE OF WILLINGEN: Missions Under the Cross. Addresses delivered at Willingen, with statements issued by the meeting. Edited by Norman Goodall THE MESSAGE OF WILLINGEN: Mission zwischen Gestern und Morgen. Vom Gestaltenwandel der Weltmission der Christenheit im Licht der Konferenz des Internationalen Missionsrats in Willingen THE MESSAGE OF WILLINGEN: Christian World Mission. An interpretation and discussion based on themes and findings of the I.M.C. World Conference, Willingen, by Cecil Northcott THE HOLY SPIRIT IN LIFE AND DOCTRINE: Die entstehung der Lehre vom Heiligen Geist, by Theodor Rüsch THE HOLY SPIRIT IN LIFE AND DOCTRINE: You and the Holy Spirit, by Stuart Oglesby THE HOLY SPIRIT IN LIFE AND DOCTRINE: Interpretation THE HOLY SPIRIT IN LIFE AND DOCTRINE: Je Crois au Saint-Esprit. Lumen Vitae. International Review of Religious Education CHRISTIAN CLASSICS: Early Christian Fathers, edited by Cyril C. Richardson LAW AND GOSPEL: Gebot und Gesetz. Zum Thema Gesetz und Evangelium, by Paul Althaus LAW AND GOSPEL: Ende des Gesetzes. Paulusstudien, by G. Bornkamm LAW AND GOSPEL: Law and Gospel in the New Testament. The Relation of Faith and Ethics in early Christianity by C. H. Dodd LAW AND GOSPEL: Gesetz und Freiheit. Das Problem des tertius usus legis bei Luther und die neutestamentliche Parainese, by Wilfried Joest THE MINISTRY OF HEALING: Lebendige Seelsorge, by Theodor Bovet THE MINISTRY OF HEALING: Man's Search for Health, by Phyllis Garlick THE MINISTRY OF HEALING: Psychology, Religion and Healing, by Leslie D. Weatherhead THE MINISTRY OF HEALING: Le ministère de la Guérison dans l'église, by Bernard Martin THE MINISTRY OF HEALING: Die Heilungskräfte Jesu. Die Heiler und der Heiland, by Ernst Jahn THE MINISTRY OF HEALING: La guérison par la foi, by Georges Crespy THE MINISTRY OF HEALING: Jean-Christophe Blumhardt et son fils, by Edmond Grin THE DILEMMA OF RELIGIOUS EDUCATION: God in Education. A Tract for the Times, by H. P. van Dusen THE DILEMMA OF RELIGIOUS EDUCATION: Faith and Education, by G. A. Buttrick THE DILEMMA OF RELIGIOUS EDUCATION: Christian Education in a Democracy, by F. E. Gaebelein THE CHRISTIAN IN HIS VOCATION: Your other Vocation, by Elton Trueblood THE CHRISTIAN IN HIS VOCATION: Luthers Lehre vom Beruf, by Gustav Wingren ETHICS AND ECONOMICS OF SOCIETY: Goals of Economic Life, edited by A. Dudley Ward ETHICS AND ECONOMICS OF SOCIETY: The Organizational Revolution. A Study in the Ethics of Economic Organization, by Kenneth E. Boulding CHRISTIANITY AND ECONOMIC LIFE: Religion and the Decline of Capitalism, by V. A. Demant CHRISTIANITY AND ECONOMIC LIFE: Social Responsibilities of the Businessman, by Howard R. Bowen CHRISTIANITY AND ECONOMIC LIFE: Religion and Economic Responsibility, by Walter G. Muelder THE RELIGIOUS MESSAGE OF THE OLD TESTAMENT: Das Alte Testament Deutsch. Neues Göttinger Bibelwerk. Edited by Volkmar Herntrich and Artur Weiser MAN IN CHRISTIAN THOUGHT: The Image of God in Man, by David Cairns